Innovation and Job Creation in a Small Open Economy. Evidence from Norwegian Manufacturing Plants 1982-92 - Tor Jakob Klette; Svein Erik Førre (Statistics Norway, Research Department, 1995)
It is often claimed that the opportunities to create new manufacturing jobs in open, high-cost economies such as Norway, are concentrated in products which are technologically advanced and knowledge intensive. This paper examines the relationship between job creation and innovation, as measured by R&D investments, in Norwegian manufacturing. We compare job creation in plants belonging to R&D firms to plants belonging to firms without R&D. We also compare job creation in plants belonging to high and low tech industries. Our data set covers more than 80 percent of manufacturing employment in Norway over the period 1982-92. The paper challenges the optimistic view about job creation in R&D intensive firms and high-tech industries. Some main findings are: (i) Net job creation is not higher in high-tech industries. (ii) There is no clear-cut positive relationship between net job creation and the R&D-intensity of the firm. (iii) There is less net job creation and less job-security in R&D-intensive firms in the late 1980s and early 1990s.
Keywords: E32; J23; J63; O32; O33; 330; R&D; innovation; job creation; job destruction.